2013
DOI: 10.1016/j.cell.2012.12.025
|View full text |Cite
|
Sign up to set email alerts
|

The Myosin Chaperone UNC-45 Is Organized in Tandem Modules to Support Myofilament Formation in C. elegans

Abstract: SummaryThe UCS (UNC-45/CRO1/She4) chaperones play an evolutionarily conserved role in promoting myosin-dependent processes, including cytokinesis, endocytosis, RNA transport, and muscle development. To investigate the protein machinery orchestrating myosin folding and assembly, we performed a comprehensive analysis of Caenorhabditis elegans UNC-45. Our structural and biochemical data demonstrate that UNC-45 forms linear protein chains that offer multiple binding sites for cooperating chaperones and client prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
211
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(219 citation statements)
references
References 72 publications
7
211
1
Order By: Relevance
“…In Sec72, it is positively charged (Fig. 1d), similarly to the TPR domains in Hop, Tom71, and Unc45, which all interact with the negatively charged C termini of chaperones (27)(28)(29). These features raise the possibility that the TPR domain of Sec72 also interacts with the negatively charged C terminus of a chaperone.…”
Section: Crystal Structure Of the Sec71-sec72 Complexmentioning
confidence: 94%
See 1 more Smart Citation
“…In Sec72, it is positively charged (Fig. 1d), similarly to the TPR domains in Hop, Tom71, and Unc45, which all interact with the negatively charged C termini of chaperones (27)(28)(29). These features raise the possibility that the TPR domain of Sec72 also interacts with the negatively charged C terminus of a chaperone.…”
Section: Crystal Structure Of the Sec71-sec72 Complexmentioning
confidence: 94%
“…2c). We next tested whether Ssa1 binds the TPR domain of Sec72 via its C termini, akin to that seen for Hsp70 binding to other TPR domains such as Hop, Tom71, and Unc45 (27)(28)(29). A GST fusion of the C-terminal lid domain of Ssa1 interacted with the TPR domain (Fig.…”
Section: The Tpr Domain Of Sec72 Binds the C-terminal Tail Of Ssa1mentioning
confidence: 99%
“…Strangely enough, while Unc45a is ubiquitously expressed and largely persists in differentiating C2C12 cells (48), the muscle-specific isoform Unc45b (48) appears to bind Hsp90 without isoform specificity (13). Nevertheless, it is noteworthy that Unc45 was linked to muscle differentiation and myosin assembly in the nematode Caenorhabditis elegans (55,56), an organism that has p23 but no Aarsd1 ortholog. Moreover, in an Unc45 mutant of the same organism, Hsp90 and other cochaperones are required for muscle integrity and motility (57).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with recent evidence that the UNC45B protein function is part of a multimeric complex. 35,36 Gazda et al 36 have demonstrated that C. elegans UNC-45 forms linear protein chains that offer multiple binding sites for cooperating chaperones and client proteins. The backbone of the UNC-45 filament is composed of the tethered superhelix ARM1-8 and TPR1-3 unit, and the UCS domain extends away from the filament axis.…”
Section: Discussionmentioning
confidence: 99%